Morphological characterization of dermal denticles of the Broadnose Sevengill Shark Notorynchus cepedianus (Elasmobranchii: Hexanchidae) - Keny Kanagusuku; Pablo Dufflocq; Angie Sánchez Rea; Ana A Huamantinco; Sergio Ramírez Amaro (Universitas Scientiarum)
Shark skin is covered by small structures called dermal denticles whose functions are diverse, such as protection, bioluminescence, hydrodynamics, among other functions. These structures have a great variety of shapes and sizes, which can be a useful approach for specimen identification as diagnostic characters between species. The present study aims to describe the dermal denticles morphology of the broadnose seven-gill shark Notorynchus cepedianus, evaluating differences among life-stage (neonate, juvenile and adult), sex and body region (dorsal and ventral). For achieving it, 39 specimens were collected at six landing points along the Peruvian coast. The dermal denticles from two body regions (dorsal and ventral) were photographed, measured (length, width, angle and density), and described using a stereoscope. Dermal denticles measures showed significant morphological differences between body regions as well as stages of development, but not between sexes. The differences are: (1) Crown shape: as the individual grows, it can be seen that the cross shape is losing, (2) Crown cusps: cusps length varied according to the stage of each individual, it was also observed that the lateral cusps are larger in dorsal than ventral region, and (3) Union peduncle - crown: adult specimens and both body regions, the observed union was very dimly and it did not have a defined shape. On the whole, these reported variations in measured traits could be useful as diagnostic characters to identify the stage of development at which the landed and marketed specimens are found.